THE CONCEPTUAL BASIS OF THE SMART EDUCATION - Natalia V. Dneprovskaya; Ekaterina A. Yankovskaya; Inessa V. Shevtsova (Открытое образование (Москва))
The paper discusses the concept of «smart», the concept of smart education, its basic elements such as smart learning, smart university smart course. The analysis of the factors affecting the formation and development of the concept of smart education. There are three aspects of Smart Education: organizational, technological, and pedagogical.